Architectural Features of the Byurakan ObservatoryComplex - Grigoryan, A. H.
The world-famous Byurakan Observatory was founded by two prominent Armenian intellectuals, Academicians Viktor Ambartsumian and Samvel Safaryan. This complex is a vivid witness to the synthesis of scientific and architectural thought, as a result of which the Observatory has become an exemplary scientific space and cultural monument. Architects Samvel Safaryan, Rafael Israelyan, Sargis Gurzadyan designed the administrative building and two telescope towers, the guesthouse building and the construction works, architects Martin Mikaelyan, Varazdat Arevshatyan, and Margarit Hayrapetyan contributed to the design of the Observatory complex. The Byurakan Observatory is a unique architectural ensemble that reflects the influences of postTamanyan Armenian national romanticism with later Soviet modernism. Thus, it is an integrated whole, each building harmonizing with historical environment, making the valuable complex a synthesis of medieval heritage and modern architectural approaches.
Keywords: Astrophysics